Proposed Quality Standards in the RTI Implementation at the LD programs: Faculty perspectives - Al Dukain, Hanan Hussain; Alsaggaf, Alwiah Abdullah (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to identify the proposed quality standards for implementing the three levels of the Response to Intervention model in learning disabilities programs in Saudi Arabia, and to identify the perceptions and beliefs of faculty members in special education programs about the essential practices that contribute to the successful use of this model. The study followed a mixed method approach, where a questionnaire and an interview were used as data collection tools. The questionnaire was applied to (32) faculty members in Saudi universities, and the interview was conducted with (3) faculty members from Saudi universities. The results of the quantitative data revealed that there are statistically significant differences between the means of the responses of the study sample in practicing the criteria (preparation, training, and planning) due to the gender variable in favor of males, and there are no statistically significant differences between the means of the responses of the study sample towards the criterion (preparation, training, and planning) due to the following variables: (years of experience- specialization- scientific rank). The results of the qualitative data showed that the participants agreed on the importance of having the necessary certificates and experience to familiarize themselves with the Response to Intervention model, and the importance of having an advisory committee to refer to in making decisions. The need for financial support and a special budget for the implementation of the Response to Intervention model and the need to ensure that the Response to Intervention model reaches the best possible quality.
Keywords: Quality; Response to Intervention Model; Learning Disability Programs; Quality Standards